2007
DOI: 10.1007/s10735-007-9156-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of quiescin Q6/sulfhydryl oxidase (QSOX) in developing mouse

Abstract: Quiescin Q6/sulfhydryl oxidases (QSOX) are revisited thiol oxidases considered to be involved in the oxidative protein folding, cell cycle control and extracellular matrix remodeling. They contain thioredoxin domains and introduce disulfide bonds into proteins and peptides, with the concomitant hydrogen peroxide formation, likely altering the redox environment. Since it is known that several developmental processes are regulated by the redox state, here we assessed if QSOX could have a role during mouse fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…1). This wide-ranged tissue distribution is in accordance with previous reports of QSOXs in human and rodent species [13, 15, 27, 38]. Of particular interest is, the pronounced epithelial expression of QSOX2 in male reproductive organs (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…1). This wide-ranged tissue distribution is in accordance with previous reports of QSOXs in human and rodent species [13, 15, 27, 38]. Of particular interest is, the pronounced epithelial expression of QSOX2 in male reproductive organs (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…RNA expression profiling showed that QSOX1 mRNA was very high in placenta and comparatively less high in the lungs (22). More recent histologic studies in the embryonic mouse suggest that QSOX1 protein expression appears in developing fetal tissue, which is consistent with the idea presented later in this review that QSOX1 is involved in tissue remodeling, invasion, and metastasis (68). In 2009, we performed IHC using anti-QSOX1 antibodies (Proteintech) to determine whether QSOX1 was over-expressed in pancreatic tumor tissues resected from patients with pancreatic cancer.…”
Section: Qsox1 Protein Expression: Tumor Versus Normalsupporting
confidence: 86%
“…Two Qsox1 mRNA splice variants have been described in human and rodents: Qsox1 variant a (Qsox-L), encoding the full-length protein containing 747 amino acids (74 kDa), and Qsox1 variant b (Qsox1-S), which encodes a truncated protein of 604 amino acids (65 kDa; Antwi et al 2009). Both QSOX1 variants have important functions on protein folding, redox homeostasis, and cell cycle control (Morel et al 2007;Portes et al 2008). The QSOX2 gene, mapped in chromosome 9, encodes a 78-kDa protein and was only described in human neuroblastoma cells under apoptosis (Wittke et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of QSOX (either QSOX1 or QSOX2; Portes et al 2008), α-actin (HHF35) and CD68 (KP1) (Santa Cruz Biotechnology, Inc; Santa Cruz, CA) expression was carried out in paraffin-embedded sections. Sections were deparaffinized and antigen retrieval was performed by boiling in Tris buffer.…”
Section: Methodsmentioning
confidence: 99%